Patellar cartilage thickness relates to knee external rotation during squatting in individuals with and without patellofemoral pain—a pilot study - Hiraku Nagahori; Kai-Yu Ho; Kai-Yu Ho (Frontiers in Sports and Active Living)
The relationship between patellofemoral cartilage morphology and knee external rotation (KER), one of the possible factors increasing patellar cartilage stress, has been rarely explored in individuals with and without patellofemoral pain (PFP). Ten individuals with PFP and 10 pain-free controls, matched for age, weight, height, and activity level, participated. Patellar cartilage morphology was assessed using 3-Tesla magnetic resonance imaging. Lower extremity kinematics during bilateral squatting at 45° of knee flexion were captured using a 3-dimensional motion capture system. Pearson and Spearman correlation coefficients were used to assess the associations between cartilage thickness (medial, lateral, and total) and peak KER, along with other peak joint angles across the three planes. Across all participants, there were significantly moderate correlations between medial cartilage thickness and KER (r = −0.48, p = 0.03), and total cartilage thickness and KER (r = −0.47, p = 0.35). In the PFP group, there was a significantly large correlation between medial cartilage thickness and KER (r = −0.66, p = 0.03). In the control group, there was a significant very large correlation between lateral cartilage thickness and KER (r = −0.79, p = 0.01) and a significant very large correlation between total cartilage thickness and KER (r = −0.75, p = 0.01). The findings suggest that thinner patellar cartilage is associated with increased KER during bilateral squatting in persons with and without PFP. Since our study focused on a double-limb activity, which may require less KER, future research should examine its impact on cartilage morphology during single-limb activities.